Exploring pre-service primary teachers’ professional knowledge for teaching science: a qualitative study - Appiani, Elisa; Montalbetti, Katia (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2025)
This study investigates specific dimensions of the professional knowledge of pre-service primary school teachers in the domain of science education, employing a predominantly qualitative research design. The theoretical framework draws upon two foundational constructs in educational research: Pedagogical Content Knowledge (PCK) (Shulman, 1986; 1987) and Professional vision (Goodwin, 1994). To date, much of the international literature has focused on the nature of PCK among in-service science teachers, particularly at the secondary level. These studies have predominantly investigated relatively “static” aspects of professional knowledge, often using interviews, surveys, and standardized instruments administered in artificial or decontextualized teaching scenarios. By contrast, limited empirical attention has been devoted to the knowledge that teachers mobilize when interpreting authentic classroom learning situations. Addressing this gap, the present research explores the “dynamic” dimensions of PCK with particular attention to the pedagogical reasoning processes that inform instructional decision-making. Methodologically, the study employs video-based reflection as a tool to elicit participants’ interpretative practices and to identify forms of Usable knowledge (Kersting et al., 2012) within the initial professional knowledge of pre-service primary school teachers. Findings indicate that the various components of PCK remain only partially integrated within the initial professional knowledge of pre-service teachers in science education. These results underscore the need for teacher education programs to engage future teachers in systematic, practice-based reflection and analysis of classroom interactions, to foster the development of a more coherent and actionable professional knowledge system.